Wild Boar Attacks on Hunting Dogs in Czechia: The Length of the Hunting Season Matters - Adámková, Jana; Lazárková, Karolína; Cukor, Jan; Brinkeová, Hana; Bartošová, Jitka; Bartoš, Luděk; Benediktová, Kateřina (Animals, 2025)
Hunting dogs are exposed to the risk of injury in driven hunts, an often-used method for managing growing wild boar numbers. This study investigated the impact of increased hunting pressure-both across the hunting season and within individual hunting events-on the risk of wild boar attacks on hunting dogs, i.e., the length of the hunting season (2.68 ± 0.76 months, mean ± standard deviation), the number of driven hunts per season (3.99 ± 0.43), the intervals between hunts (17.85 ± 4.83 days), the number of wild boars harvested per season (14.46 ± 13.10), and the number of participants (23.8 ± 10.69) and dogs (4.56 ± 2.66) involved per hunt. The data were collected via a retrospective questionnaire survey. The information-theoretic approach (IT-AIC) and GLMM were employed to estimate the factors' effects on the number of wild boar attacks on dogs reported in 40 hunting grounds in five consecutive hunting seasons (2.60 ± 5.07 attacks per hunting season in a hunting ground). The number of attacks only increased with the length of the hunting season. The best model did not include other factors, such as shorter intervals between hunts, a higher number of driven hunts, wild boars harvested, or participants. The respondents reported 150 injuries by wild boars during 797 driven hunts. Most injuries were mild (73.8%), with fewer severe (18.8%) and fatal (7.4%) cases. Further investigation into wild boar and hunting dog interactions is necessary for constructing strategies to improve hunting practices and reduce dog injury risks.
Keywords: seasonal evaluation; Canis familiaris; animal welfare; Sus scrofa; wildlife management; animal aggression; injuries